A smoothed void fraction method for CFD-DEM simulation of packed pebble beds with particle thermal radiation. (March 2018) - Wu, Hao; Gui, Nan; Yang, Xingtuan; Tu, Jiyuan; Jiang, Shengyao
Highlights: Smoothed void fraction method (SVF) is proposed for a sub-particle CFD-DEM model. Step function is replaced by diffusion function to improve simulation convergence. SVF is validated, and virtual symmetric point method agrees with practical wall effect. SVF used for HTR-10 benchmark problem on subparticle mesh agrees with THERMIX. Effect of mesh size & smoothing degree are analyzed and optimum values are suggested. Abstract: The core of the high temperature gas-cooled reactor (HTGR) is a dense packed pebble bed with large-sized fuel spheres. In the CFD-DEM simulations of fluid-particle systems on sub-particle scale mesh, a smoothed void fraction method (SVFM) is developed to compute the void fraction field based on the particle position and volume. A diffusion function is obtained analytically as a spatial distribution function of particle volume in SVFM, which converges to the step-function-type distribution of particle volume in the sub-particle-scale divided finite volume method (DFVM) when the smoothing degree goes to 0. In validation by a spout fluidized bed when the cell size is less than the particle diameter, it is shown that SVFM is preferable to DFVM for the CFD-DEM simulation since it is in better agreement with the experimental measurements. Moreover, the CFD-DEM simulation using the SVFM on sub-particle scale meshes is performed for the benchmark problem of the HTR-10 reactor. The numerical results at the smoothing degree of η = 0.5 are in good agreement with the empirical code of THERMIX – which is based on experimental measurements. In addition, the discussion indicates that the smoothing degree in SVFM is recommended to be 0.5–0.7 according to the void fraction distribution of Voronoi-tessellation.